Consistency checks of results from a Monte Carlo code intercomparison for emitted electron spectra and energy deposition around a single gold nanoparticle irradiated by X-rays. (September 2021) - Rabus, H.; Li, W.B.; Nettelbeck, H.; Schuemann, J.; Villagrasa, C.; Beuve, M.; Di Maria, S.; Heide, B.; Klapproth, A.P.; Poignant, F.; Qiu, R.; Rudek, B.
Abstract: Organized by the European Radiation Dosimetry Group (EURADOS), a Monte Carlo code intercomparison exercise was conducted where participants simulated the emitted electron spectra and energy deposition around a single gold nanoparticle (GNP) irradiated by X-rays. In the exercise, the participants scored energy imparted in concentric spherical shells around a spherical volume filled with gold or water as well as the spectral distribution of electrons leaving the GNP. Initially, only the ratio of energy deposition with and without GNP was to be reported. During the evaluation of the exercise, however, the data for energy deposition in the presence and absence of the GNP were also requested. A GNP size of 50 nm and 100 nm diameter was considered as well as two different X-ray spectra (50 kVp and 100 kVp). This introduced a redundancy that can be used to cross-validate the internal consistency of the simulation results. In this work, evaluation of the reported results is presented in terms of integral quantities that can be benchmarked against values obtained from physical properties of the radiation spectra and materials involved. The impact of different interaction cross-section datasets and their implementation in the different Monte Carlo codes is also discussed. Highlights: Summary of Monte Carlo code intercomparison for single nanoparticles and x rays. Set of consistency checks allowed identifying and correcting normalization problems. Good agreement between integral results of simulations that passed the consistency checks. All codes predict about 2 electrons with energy >100 eV emitted per photon interaction. Up to about a factor of 3 differences in the total number of emitted electrons.